A XML based, user-centered privacy model in pervasive computing systems - Dehghantanha, Ali; Mahmod, Ramlan; Udzir, Nur Izura (2009)
The fact that pervasive systems are typically embedded and invisible makes it difficult for users to know when, where, and how these devices are collecting data. So privacy is a major issue for pervasive computing applications and several privacy models have been proposed for pervasive environments. In this paper we present a XML based User-centered Privacy Model (UPM) which provides content, identity, location, and time privacy with low unobtrusiveness